Vilcunia periglacialis Cei & Scolaro, 1982 (Reptilia: Lacertilia: Iguania): proposed conservation of the specific name. Case 3219 - Scolaro, Jose Alejandro (2001)
The conservation of the specific name Liolaemus (Vilcunia) periglacialis is proposed, over Liolaemus hatcheri. The previous nomination was Vilcunia periglacialis but recently with the redescription of Liolaemus hatcheri this name was proposed as precedence in relation to the conspecific taxon L.periglacialis(Cei & Scolaro 1982) described many decades later. However, Scolaro & Cei claimed that the original description of L. hatcheri was based in a series of Liolaemus individuals belonging to three different species (L. hatcheri, L. lineomaculatus and L. kingii), with limited or no details on the collection locality. Also, the name periglacialis has largely been used in many herpetological studies, in contrast to the name hatcheri, cited in only a few works.Teherefore, the name periglacialis (commonly under the genus Vilcunia Donoso-Barros & Cei 1971) was not only based in an official type series with exact details on the type locality, but also has been widely used in several publications.